Gender Equality in the HMNS Product Campaign "HMNS Perfection" Edition - Alfaini, Fitri; Fitrinanda An Nur (POPULIKA, 2024)
This research aims to explain the phenomenon focusing on gender issues and gender equality in HMNS product advertisements. This issue has spread and become a growing trend in society. The problem of gender equality is always inherent in Indonesian society regarding the division of work areas. As a result, inequality between men and women often occurs. The root of the problem is that society cannot separate sex and gender. Sex and gender are considered the same thing, so various stereotypes and gender discrimination emerge. Men are always associated with being strong, independent, and involved in the public domain. On the other hand, women are always close to the domestic area and are always associated with a gentle nature. This research is qualitative, using an analytical method, namely qualitative content analysis, and to explain the form of gender equality, the researcher uses the theory of gender inequality from Fakih (2008), namely stereotypes, discrimination, subordination, and double burden. The object of this research is the HMNS advertisement for the "HMNS Perfection" edition. Data collection in this research is observation, documentation, and literature study. The data analysis technique in this research is that first, the researcher will group the data obtained via social media X via the official HMNS account. After that, the researcher conducted data reduction, presented the data by analyzing it, and then drew conclusions. The research results show that HMNS, as a local brand, educates about gender equality through its post entitled 'Perfection' by showing that men can make their choices without social labeling (stereotypes), the absence of gender discrimination, subordination, and double burdens in the HMNS Perfection campaign. Keywords: Equality; Gender; HMNS; Advertisement; X